Monovalent cation/sodium: proton antiporter proteins of Ehrlichia chaffeensis - Wei, Lanjing (Kansas State University, 2018)
Anaplasmataceae family rickettsial bacteria are mostly vector-transmitted pathogens causing important diseases in several vertebrates, including humans, canines, and ruminants. Ehrlichia chaffeensis, a tick-transmitted intraphagosomal rickettsial bacterium, is the causative agent of human monocytic ehrlichiosis (HME). Little is known about how this and other related rickettsial organisms are able to reside and replicate within an acidified phagosome environment. Similarly, it is unclear how the infectious form of the bacterium maintains pH homeostasis in the extracellular milieu where the pH is about 7.35-7.45, before its infection to a naïve host cell. Sodium/cation: proton antiporters are integral membrane proteins reported from a wide range of species. They exchange sodium or other monovalent cations against protons across a plasma membrane in maintaining the cytoplasmic pH of a cell. We recently described a mutation within the Ech_0379 gene of E. chaffeensis that is predicted to encode for a Na+/H+ antiporter protein. The mutation caused the attenuated growth of the organism in vertebrate hosts, resulting in a reduced level of the bacterial presence in the circulation. In this study, we evaluated several antiporter protein genes of E. chaffeensis. Its genome contains 10 coding sequences encoding for polypeptides which may form at least six functional proteins. To define their function, a sodium sensitive Escherichia coli strain having a mutation in two of its three antiporter protein genes (EP432) is used to carry out the functional complementation assay with E. chaffeensis genes from their respective promoters. The EP432 strain has a growth defect during its replication in the presence of NaCl that can be restored with functional complementation. All six E. chaffeensis genes could complement the growth defect of EP432 under acidic pH, while Ech_0379 and Ech_0179 also complemented at basic pH. Ech_0179 complemented at neutral pH as well. The complementation of all genes at neutral and basic pHs, except Ech_0179 and Ech_0379, made EP432 E. coli strain be more sensitive to the presence of 200 mM NaCl. The channeling activity is verified independently by constructing a proteoliposome in vitro with the recombinant protein Ech_0379. The recombinant protein showed antiporter activity at all three pHs in the presence of 100 or 200 mM NaCl when assessed using the recombinant proteoliposome. This research is the first description of antiporter proteins of E. chaffeensis.
Keywords: Sodium/proton antiporterEhrlichia chaffeensis